Effect of Cooking Method on The Physicochemical Properties of Tomatoes - Teh, Arnida Hani; Ting, Teo Wan (Malaysian Applied Biology, 2024)
The cooking process influences the chemical and physical changes in food due to the increase in temperature. It also alters the appearance, taste, color, and texture of food either positively or negatively. Therefore, this study was done to determine the effect of cooking methods on the physicochemical properties and the retention of antioxidant content in tomatoes. The cooking conditions used were boiling at 100°C for 6 min, frying at 230°C for 4.5 min, baking at 175°C for 25 min, and cooking with an air fryer at 200°C for 15 min. Physicochemical characteristics (cooking loss, ash, crude fiber, firmness, color, pH value & total soluble solids) were measured. Antioxidant properties (antioxidant activity, total phenolic content, lycopene content, and ascorbic acid content) were also determined. There were significant differences (p<0.05) for ash, color, pH value, and total soluble solid, while no significant difference (p>0.05) was observed for cooking loss, crude fiber, and firmness. Different cooking methods had shown a significant difference (p<0.05) against all tests for determining antioxidant activity, total phenolic content, lycopene content, and ascorbic acid content. Air frying is the best cooking method to preserve the physicochemical properties of tomatoes, compared to other methods employed. Hence, it can be concluded that different cooking methods have different effects on the physicochemical properties of tomatoes.